APPROPRIATE AND INAPPROPRIATE USES OF HUMOR BY TEACHERS AND THE EFFECT OF IT IN LEARNING - Fitriah Fitriah (English Department of Faculty of Tarbiyah and Teacher Training, 2012)
This study investigated the students’ view of the appropriate and inappropriate use of humor in the classroom and the effect of it in students’ learning. There were 20 postgraduate students participating in the study, and they were asked to list several examples of suitable and unsuitable use of humor in the classroom and consider the effect of humor in the learning. The result informed that joking about sexual matters, religion, sexist issues, racism, appearance, sarcasm, ethnicity and cultural value was claimed as inappropriate humor, and 83% of students commented that these types of humor had a negative impact on their learning. However, humor related to the topic being taught, cartoons, funny stories, puns, language mistakes was perceived as appropriate, and 94% of them believed that these types of humor affect positively in the learning.